Designing a combined liothyronine (LT3), L- thyroxine (LT4) trial in symptomatic hypothyroid subjects on LT4 - the importance of patient selection, choice of LT3 and trial design - Premawardhana, Lakdasa D.; Taylor, Peter Nicholas; Okosieme, Onyebuchi E.; Adlan, Mohamed A.; Obuobie, Emmanuel K.; Dayan, Colin Mark (Frontiers in Endocrinology, 2023)
10-15% of subjects with hypothyroidism on L-thyroxine (LT4) alone, have persistent symptoms affecting their quality of life (QoL). Although the cause for this is unclear, there is evidence that "tissue T3 lack" may be responsible. Therefore, combining liothyronine (LT3) with LT4 should help. However, randomised controlled trials (RCT), have not established greater efficacy for LT3+LT4 combination in these subjects compared to LT4 alone. While trial design may have been responsible, the use of unphysiological, short acting LT3 preparations and non-thyroid specific patient reported outcome measures (PROMs) may have contributed. We recommend attention to the following aspects of trial design for RCTs of LT3+LT4 compared to LT4 alone -(a) Subject selection -(i) measurable symptoms (disadvantages should be recognised); (ii) using a validated thyroid specific PROM such as ThyPRO39 or the Composite scale derived from it; (iii) those taking over 1.2µg/day or 100µg/day (for pragmatic reasons) of LT4 defining a population likely without intrinsic thyroid activity who depend on exogenous LT4; (iv) recruiting a preponderance of subjects with autoimmune thyroiditis increasing generalisability; and (v) those with a high symptom load with a greater response to combination therapy e.g. those with the deiodinase 2 polymorphism. (b) The use of physiological LT3 preparations producing pharmacokinetic similarities to T3 profiles in unaffected subjects -2 long acting LT3 preparations are currently available which need testing in phase 2b/3 RCTs. (c) The superiority of a crossover design in limiting numbers and costs while maintaining statistical power and ensuring all subjects experience the investigative medication. Word count 248/250